Pemanfaatan Remitansi Pada Keluarga Migran di Pedesaan Sulawesi Selatan: Perspektif Tindakan Sosial Weberian - Gita Kartika Bahti; Idham Irwansyah Idrus; Ulfa Utami Mappe (Prodi Sosiologi FISIP Universitas Teuku Umar, 2026)
This study analyses the utilization of remittances among migrant families in Bontominasa Village, Bulukumba Regency, through the perspective of Max Weber’s social action theory. The research focuses on the socio-economic background of migrant families, patterns of remittance utilization, and their implications for household welfare. This study departs from the social phenomenon of labour migration caused by economic pressures and limited employment opportunities in rural areas. Weber’s theory of social action is used to explain that migration and remittance utilization represent rational-instrumental actions undertaken by families to achieve economic security and social mobility. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews with eight remittance-receiving families, observations, and documentation. The findings indicate that migration decisions were strongly influenced by economic hardship following mass layoffs in the rubber plantation sector. Remittances were mainly utilized for household consumption, including basic daily needs, children’s education, healthcare, housing improvement, and debt repayment. In addition, a smaller portion of remittances was allocated for productive purposes such as small business capital, livestock investment, and savings. The study also found that remittances contributed to improving family welfare and social status within the community. However, dependence on remittance income and the social consequences of prolonged family separation remain significant challenges for migrant households. The study implies the importance of strengthening financial literacy, productive economic empowerment, and community-based social support programs to encourage more sustainable and welfare-oriented remittance management among migrant families.